Driving quality in informatics fulfilling the promise - Courtney, Karen L.; Kuo, Alex; Shabestari, Omid (Studies in health technology and informatics, 2015)
Although the data in healthcare comes from and relates to patients, it has generally been the clinician and not the patient who has been seen as the end-user of health information or health information technology.